ANALISIS KEAMANAN DAN KEHALALAN PRODUK HANDBODY RACIKAN DITINJAU DARI PERSPEKTIF EKONOMI SYARIAH - Devita Firani; Siti Nikmah Marzuki; Fitriani Fitriani (IKRAITH-EKONOMIKA, 2026)
This study aims to analyze the safety and halal status of homemade body lotion products circulating in the community from the perspective of Islamic economics. The study was motivated by the widespread use of homemade body lotions, which are perceived to produce faster results than other cosmetic products, yet still raise concerns regarding their safety and halal compliance. This research employed a field research method using a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving consumers as well as producers or sellers of homemade body lotion in Bone Regency. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the use of homemade body lotion is driven by consumers' desire to achieve quick results, social environmental influences, social media exposure, and relatively affordable prices. From the safety perspective, homemade body lotion products do not provide adequate safety assurance because most of them lack distribution permits from the Indonesian Food and Drug Authority (BPOM), have not undergone laboratory testing, do not follow standardized formulation measurements, and have caused side effects among some users, including redness, itching, and skin irritation. From the halal perspective, these products do not have confirmed halal status because they are not officially halal-certified and do not provide complete ingredient information. From the perspective of Islamic economics, these conditions involve elements of gharar (uncertainty) and have the potential to cause harm (mudarat) to consumers. This study concludes that homemade body lotion products circulating in the community do not fully comply with the principles of Islamic economics, particularly the principles of halālan ṭayyiban, hifz al-nafs (protection of life), hifz al-din (protection of religion), ihtiyāṭ (prudence), transparency, and the prohibition against causing harm. Therefore, greater consumer awareness is needed in selecting cosmetic products that are safe and halal, along with stricter supervision of the distribution of homemade cosmetic products.